2015
DOI: 10.1016/j.biopsych.2014.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Interneurons Are Necessary for Coordinated Activity During Reversal Learning in Orbitofrontal Cortex

Abstract: Background Cerebral cortical GABAergic interneuron dysfunction is hypothesized to lead to cognitive deficits co-morbid with human neuropsychiatric disorders, including schizophrenia, autism and epilepsy. We have previously shown that mice that harbor mutations in the Plaur gene, which is associated with schizophrenia, have deficits in frontal cortical parvalbumin expressing interneurons. Plaur mice have impaired reversal learning, similar to deficits observed in patients with schizophrenia. Methods We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 72 publications
4
51
1
Order By: Relevance
“…For example, Schoenbaum et al (2000) performed simultaneous recordings of neurons in LO/VO and basolateral amygdala during an odor discrimination task and observed increases in correlated activity during reversal of an initially established stimulus-outcome association (odor-sucrose). A recent report from Bissonette et al (2014b) also found that LO/VO neurons in the mouse respond to odor discrimination performance, reversal performance, or exclusively with respect to the expected outcome.…”
Section: Reversal Learningmentioning
confidence: 89%
“…For example, Schoenbaum et al (2000) performed simultaneous recordings of neurons in LO/VO and basolateral amygdala during an odor discrimination task and observed increases in correlated activity during reversal of an initially established stimulus-outcome association (odor-sucrose). A recent report from Bissonette et al (2014b) also found that LO/VO neurons in the mouse respond to odor discrimination performance, reversal performance, or exclusively with respect to the expected outcome.…”
Section: Reversal Learningmentioning
confidence: 89%
“…The ability to initiate, select, and shift action involves the ventromedial and orbitofrontal regions of the prefrontal cortex, and the dorsal striatum Hamilton and Brigman 2015). Reversal learning is thought to depend on medial prefrontal cortex, orbitofrontal cortex, and interconnected subcortical areas, most notably dorsal striatum (Ragozzino 2007;Bissonette et al 2008Bissonette et al , 2015Brigman and Rothblat 2008). Deficits in pairwise discrimination and reversal learning in the Dolmetsch 16p11.2+/2 could be a consequence of cortical and striatal defects.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether the alterations in interneurons observed in schizophrenia cause abnormal γ oscillations and thereby contribute to cognitive deficits, or whether alterations in PV interneurons and γ oscillations represent incidental or compensatory changes. While many studies have found important schizophrenia-related abnormalities in mutant mice with disruptions in cortical GABAergic interneurons (Belforte et al, 2010; Bissonette et al, 2014), including specific disruptions of FSINs (Carlen et al, 2012; Del Pino et al, 2013; Korotkova et al, 2010), none have reported the deficits in task-evoked γ oscillations that are hypothesized to mediate cognitive deficits (it is unclear whether they explicitly looked for and did not find deficient task-evoked γ oscillations). By contrast, NMDAR antagonists can both increase baseline γ oscillations and decrease sensory stimulus-evoked γ power (Saunders et al, 2012).…”
Section: Introductionmentioning
confidence: 99%